Ecuador - Country Note on Climate Change Aspects in Agriculture - World Bank (Washington, DC, 2012)
This country note briefly summarizes information relevant to both climate change and agriculture in Ecuador, with focus on policy developments (including action plans and programs) and institutional make-up. Like most countries in Latin America, Ecuador has submitted one national communication to the United Nations Framework Convention on Climate Change (UNFCCC) with a second one under preparation. Land use change and forestry are the largest contributors to greenhouse gases (GHG) emissions in the country. The emission reduction potential of the agricultural sector (including land use change and forestry) is significant and not yet sufficiently explored in the country. Agriculture is highly vulnerable to weather variability. Sustainable water management and climate-sensitive insurance coverage for agricultural production can reduce some of the observed vulnerabilities in the country.